2021
DOI: 10.1007/s00436-020-07026-2
|View full text |Cite
|
Sign up to set email alerts
|

Human filariasis—contributions of the Litomosoides sigmodontis and Acanthocheilonema viteae animal model

Abstract: Filariae are vector-borne parasitic nematodes that are endemic worldwide, in tropical and subtropical regions. Important human filariae spp. include Onchocerca volvulus, Wuchereria bancrofti and Brugia spp., and Loa loa and Mansonella spp. causing onchocerciasis (river blindness), lymphatic filariasis (lymphedema and hydrocele), loiasis (eye worm), and mansonelliasis, respectively. It is estimated that over 1 billion individuals live in endemic regions where filarial diseases are a public health concern contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 239 publications
(311 reference statements)
1
28
0
Order By: Relevance
“…In the genus Acanthocheilonema this variation in vectors is particularly high. While the rodent parasite Acanthocheilonema viteae uses the soft tick Ornithodorus tartakovskyi [ 106 ], A. dracunculoides infecting domestic dogs is transmitted by the brown dog tick Rhipicephalus sanguineus [ 107 , 108 ] and the louse fly H. longipennis [ 38 ]. The other Acanthocheilonema species commonly found in domestic dogs, A. reconditum , uses various fleas (including Ctenocephalides spp.…”
Section: Discussionmentioning
confidence: 99%
“…In the genus Acanthocheilonema this variation in vectors is particularly high. While the rodent parasite Acanthocheilonema viteae uses the soft tick Ornithodorus tartakovskyi [ 106 ], A. dracunculoides infecting domestic dogs is transmitted by the brown dog tick Rhipicephalus sanguineus [ 107 , 108 ] and the louse fly H. longipennis [ 38 ]. The other Acanthocheilonema species commonly found in domestic dogs, A. reconditum , uses various fleas (including Ctenocephalides spp.…”
Section: Discussionmentioning
confidence: 99%
“…From this screen, Tylosin A (TylA), a commercial veterinary macrolide antibiotic, was identified as novel lead. TylA is a macrolide antibiotic that is active mostly against Gram-positive bacteria and mycoplasmas by binding to the 50S ribosomal subunit, inhibiting protein synthesis (Risch et al 2021). TylA has displayed potent anti-Wolbachia activity with an in vitro EC 50 of 28 nM, but TylA is characterized by poor oral bioavailability resulting from low permeability (< 0.1•10 −6 cm/s) in a canine kidney cell monolayer system (MDR-MDCK).…”
Section: Tylamac (Abbv-4083)mentioning
confidence: 99%
“…In contrast, within the same laboratory but differences in culture media, the L3 stage of L. sigmodontis was less sensitive than microfilariae as none of the tested emodepside concentrations were able to inhibit L3 L. sigmodontis completely. L. sigmodontis is used as a rodent model for human filarial infections ( Hübner et al, 2009 ; Risch et al, 2021 ), and previous in vivo studies of emodepside in a rodent model have already indicated that emodepside is not effective at killing larval and pre-adult stages of L. sigmodontis or B. malayi ( Zahner et al, 2001a ). Only microfilariae of B. malayi were tested in this study, and therefore the in vitro susceptibility of the L3 stage of B. malayi remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the filaricidal activity spectrum of emodepside as part of the preclinical package, this study investigates emodepside in vitro susceptibility of a range of filariae, including Acanthocheilonema viteae, B. malayi , B. pahangi , Dirofilaria immitis, Litomosoides sigmodontis , O. gutturosa , and O. lienalis. These species are commonly used as model organisms for human filariasis ( Townson et al, 2005 ; Morris et al, 2013 ; Risch et al, 2021 ) . Different stages including microfilariae, third-stage (L3) and fourth-stage (L4) larvae, as well as adult male and female worms, were exposed to varying concentrations of emodepside in order to measure drug effects on helminth motility, using established and adapted protocols ( Tagboto and Townson, 1996 ; Townson et al, 2007 ; Storey et al, 2014 ; Maclean et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%